Authentic Assessment on Fiqh Subjects at Class XI IIk 2 MA Al Ma'had An-Nur Bantul - Syarifah Nur Hidayati; Ahmad Shofiyuddin Ichsan; Mujawazah Mujawazah (Edunesia: Jurnal Ilmiah Pendidikan, 2022)
This research aimed to find out how the implementation of authentic assessment in online learning for fiqh subjects in class XI IIK 2 MA Al Ma'had An-Nur Bantul. This research was qualitative research with data collection techniques using observation, interviews, and documentation. While the data analysis method used the theory of Miles and Huberman. Not only that, the checking technique of the data validity used several criteria. The research results revealed that (1) includes competency assessment during the online learning process, the teacher saw student activity when participating in learning through Google Meet. (2) Knowledge Competence using written assessment instrument techniques and assignments or projects. (3) The psychomotor competence of students to practice creative and innovative skills. The assessment results could be seen from two things, namely, students were able to understand the material provided, and students were trained in honest behavior. The supporting factors were teachers, school facilities, and quota assistance. While the inhibiting factors were that the assessment was not very effective during the pandemic, learning was not conducive, and the lack of communication between teachers and students so that the administrators were overwhelmed in dealing with existing problems